La idea de lo tremendo - Romero Moscoso, Alberto Carlos (CALLE14: revista de investigación en el campo del arte, 2011)
The author reflects on contemporary aesthetics, considering the ideas of the beautiful and the proper, besides the idea of aesthetics itself, from an introduction and discussion of the idea of the tremendous in Wittgenstein, according to which the aesthetical judgment is understood as an ethical judgment. Following this road, the article proposes, in order to allow a place for the spectator in the thought about the work of art, a place in which the judgement remains private and does not constitute an evaluation.